Surface and Subsurface Quality Assessment of Polished Lu2O3 Single Crystal Using Quasi-Brewster Angle Technique - Yao, Chengyuan; Shen, Wanfu; Hu, Xiaodong; Hu, Chunguang (Frontiers in Physics, 2021)
The sesquioxide Lu2O3 single crystal has attracted tremendous attention as potential host material for high-power solid-state lasers. As polishing is the terminal process of conventional ultra-precision machining, the quality of polished crystal directly impacts the crucial performance indicators of optics. The high melting point of Lu2O3 single crystal makes crystal preparation difficult. Therefore, investigations on the surface/subsurface quality inspection of polished Lu2O3 single crystal are scarce. In this paper, we utilize the quasi-Brewster angle technique (qBAT) based on ellipsometry to inspect the quality of polished Lu2O3 single crystal, achieving fast, nondestructive, and high-sensitive surface/subsurface damage assessment. A systematic crystal processing scheme is designed and polished Lu2O3 crystal samples are obtained. To verify the results of qBAT, the surface and subsurface quality are tested using optical profilometer and transmission electron microscope, respectively. The consistency of the test results demonstrates the feasibility, high sensitivity and accuracy of the qBAT. To our knowledge, this is the first time that the qBAT is applied to investigate the polished surface/subsurface quality of Lu2O3 single crystal. In conclusion, this method provides a powerful approach to the high-precision characterization of the surface/subsurface quality of Lu2O3 single crystal, and has significant potential for material property study and process optimization during ultra-precision machining.